Structural assessment of masonry arch bridges by combination of non-destructive testing techniques and three-dimensional numerical modelling: Application to Vilanova bridge. (1st October 2017) - Conde, Borja; Ramos, Luís F.; Oliveira, Daniel V.; Riveiro, Belén; Solla, Mercedes
Highlights: A comprehensive non-destructive testing campaign of an historical stone arch bridge is presented. A three-dimensional non-linear finite element modelling strategy for masonry arch bridges is adopted. Finite element model updating is performed through optimization procedures. The key role that fill materials play in the structural behavior of masonry arch bridges is demonstrated. The critical importance that transverse effects have on the strength capacity of masonry arch bridges is evidenced. Abstract: In this work a multidisciplinary approach for the structural assessment of masonry arch bridges is presented. The Vilanova Bridge, located in Galicia, northwest of Spain, is considered for the implementation of the methodology. A comprehensive field survey fully based on non-destructive testing techniques, which integrates laser scanning, ground penetration radar, sonic tests and ambient vibration testing, is proposed. It provides all the necessary geometric data to build an accurate and detailed three-dimensional finite element model. The calibration of the model is then carried out through the coupling with an optimization algorithm, which minimizes the discrepancies with respect to the experimentally obtained modal properties. The structural analysis of the bridge is addressed in the last stage. A sensitivity analysis involving different loading scenarios and the plausible variation of the masonry and soil material properties is performed. The results demonstrate the significant influence of tensile non-linear properties of masonry, but also the key role played by fill materials on the arch bridge performance. Lastly, the advantages of adopting a three-dimensional modelling approach are also pointed out, since the apparition of critical transverse effects in the response of the structure is successfully captured by the developed numerical model.